Ligand Diffusion Enables Force‐Independent Cell Adhesion via Activating α5β1 Integrin and Initiating Rac and RhoA Signaling. Issue 29 (14th June 2020) - Yu, Leixiao; Hou, Yong; Xie, Wenyan; Camacho, Jose Luis Cuellar; Cheng, Chong; Holle, Andrew; Young, Jennifer; Trappmann, Britta; Zhao, Weifeng; Melzig, Matthias F.; Cavalcanti‐Adam, Elisabetta A.; Zhao, Changsheng; et al.
Abstract: Cells reside in a dynamic microenvironment in which adhesive ligand availability, density, and diffusivity are key factors regulating cellular behavior. Here, the cellular response to integrin‐binding ligand dynamics by directly controlling ligand diffusivity via tunable ligand–surface interactions is investigated. Interestingly, cell spread on the surfaces with fast ligand diffusion is independent of myosin‐based force generation. Fast ligand diffusion enhances α5β1 but not αvβ3 integrin activation and initiates Rac and RhoA but not ROCK signaling, resulting in lamellipodium‐based fast cell spreading. Meanwhile, on surfaces with immobile ligands, αvβ3 and α5β1 integrins synergistically initiate intracellular‐force‐based canonical mechanotransduction pathways to enhance cell adhesion and osteogenic differentiation of stem cells. These results indicate the presence of heretofore‐unrecognized pathways, distinct from canonical actomyosin‐driven mechanisms, that are capable of promoting cell adhesion. Abstract : Cell adhesion and stem cell fate specification exhibit unexpected behaviors in response to ligand diffusivity. Fast ligand diffusion enables cell adhesion independent of myosin‐based force generation. An atypical pathway utilizing α5β1 integrin, RhoA, and Rac is detected to induce cell adhesion in such situations where αvβ3 integrin‐related mechanotransduction pathways are inactive.